Analytical analysis of a rigid rotor mounted on three hydrostatic pads lubricated with micropolar fluids. (June 2019) - Benariba, Aboubakeur; Bouzidane, Ahmed; Thomas, Marc
Analytical analysis of rigid rotor set vertically, supported by a new hydrostatic squeeze film damper consisting in three hydrostatic pads fed through three capillary restrictors operating with micropolar lubricant is presented. The modified Reynolds equation is obtained using the micropolar lubrication theory and solving it analytically. The calculation of the flow rate, dimensionless vibratory amplitude and amplitude of transmitted forces are determined by resolving the equations of rotor motion using nonlinear methods. It has been observed that a rigid rotor operating with micropolar lubricant shows an increase in the value of transmitted forces at high speeds and a reduction in the value of vibratory response at critical speed when compared to a corresponding similar rigid rotor operating with Newtonian lubricant.